1995
DOI: 10.1152/ajpgi.1995.268.4.g695
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of capsaicin-sensitive primary afferent fibers in regulation of jejunal alanine absorption

Abstract: Capsaicin-sensitive primary afferent fibers (CSPA) in the small intestine regulate many functions through the release of peptides and neurotransmitters. This study was undertaken to assess the role of CSPA in the regulation of jejunal alanine absorption in the rat. In a series of in vivo experiments, the effects of the sensory neurotoxin capsaicin on small intestinal alanine absorption were evaluated. In vitro experiments were also done to study its effects on alanine uptake by isolated jejunal strips and muco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Studies have shown that intraluminal capsaicin infusion (which is acutely excitatory on vagal afferents) in the short term suppresses alanine transport and expression of the PepT1 peptide transporter (2,18). In contrast, vagal deafferentation leads to upregulation of alanine transport (25). Functional studies (using brush-border membrane vesicle uptake of glucose) have demonstrated that vagal deafferentation prevents upregulation of glucose transport after switching to a highcarbohydrate diet in guinea pigs (3).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that intraluminal capsaicin infusion (which is acutely excitatory on vagal afferents) in the short term suppresses alanine transport and expression of the PepT1 peptide transporter (2,18). In contrast, vagal deafferentation leads to upregulation of alanine transport (25). Functional studies (using brush-border membrane vesicle uptake of glucose) have demonstrated that vagal deafferentation prevents upregulation of glucose transport after switching to a highcarbohydrate diet in guinea pigs (3).…”
Section: Discussionmentioning
confidence: 99%
“…The ENS, one of the major parts of the autonomic nervous system, is involved in the regulation of gastrointestinal transport of fluid (19,29) and amino acids (5,41). Changes in the ENS and extrinsic innervation in colitis have been described, as evidenced by an increase in c-Fos in myenteric neurons, enteric glia, brain stem, and spinal cord in formalin-induced colitis in rats (31,33) and by an increase in ileal myoelectric activity in TNBS-treated rats (3).…”
Section: Discussionmentioning
confidence: 99%
“…Aliquots of the initial and effluent solutions were assayed for phenol red concentration and radioactivity content. Absorption was calculated from the rate of disappearance of labeled amino acid from the perfusate solution, taking into account water transport as measured by the change of phenol red concentrations (9,40,41).…”
Section: Intestinal Perfusion For Measurement Of Amino Acid Absorptionmentioning
confidence: 99%
“…1 filter paper, its wet weight was determined, and then the strip was extracted in 2 ml of 0.1 M HNO 3 for at least 4 h. Aliquots of the tissue extracts and incubation media were counted for their [ 14 C]Ala content in a liquid scintillation counter. From the data obtained, intracellular concentration of Ala was calculated after correction for the extracellular space by using a trace amount of [ 3 H]inulin as an extracellular marker (41). Values of intracellular Ala concentration were plotted against Ala concentration in the incubation medium.…”
Section: Intestinal Perfusion For Measurement Of Amino Acid Absorptionmentioning
confidence: 99%